Pengaruh penetapan harga terhadap minat beli konsumen pada apotek maksum farma maja Kabupaten Majalengka - Yakin, Muhamad Ainul; Tia Aprilia Susnita (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The purpose of conducting this research is to collect information that will be used to analyze the effect of pricing on consumer buying interest at Maksum Farma Maja Pharmacy, Majalengka Regency. And is expected to assist the company in solving the problems faced following the topic taken by the author by analyzing, especially information and data regarding the effect of pricing on consumer buying interest. This research was conducted at Maksum Farma Maja Pharmacy, Majalengka Regency. The method used in this research is descriptive and verification method with a qualitative approach. The unit of analysis in this study is pricing as an independent variable and consumer buying interest as the dependent variable. The sampling of 96 respondents in this study used the accidental sampling method. To determine the effect of price-fixing on consumer buying interest, the statistical analysis uses simple linear regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing using a t-test. Based on the analysis results, there is an influence between price-fixing on consumer buying interest. This is evidenced by the results of the calculation of tcount of 9.5592, which is more significant than ttable which is 1.66123 for the two-party test, the significant level is 0.05 at DK = 94, then Ha is accepted, that is, thus then the author can conclude that pricing can support consumer buying interest. The result of the calculation of the correlation value is 0.7021. This value indicates the strength of the relationship is included in the category of a strong relationship. From the analysis of the coefficient of determination, it is known that the value of R square is 0.4929 or 49.29%. This shows that the price-setting influences the variable of consumer buying interest by 49.29%. The rest, amounting to 50.71%, is determined by factors outside this research. From the calculation of the regression coefficient, the equation Y = 2.89 + 0.42X is obtained. The regression coefficient of 0.42 states that every increase (because b is marked +) 1 unit of pricing will increase consumer buying interest by 0.42 units